Different methods evaluation of antioxidant properties of Myrtus communis extract and its fractions - Soheila Moein; Mahmoodreza Moein; Fatemeh Farmani; Zahra Sabahi (Shiraz University of Medical Sciences, 2015)
Myrtus communis L. is a plant traditionally used as an antiseptic and disinfectant drug. In this research, the antioxidant activity of Myrtus communis was assayed by evaluating radical scavenging activity, reducing power, FRAP method and determination of phenolic compounds. The methanolic extract of leaves of Myrtus communis was fractionated by using petroleum ether, chloroform, ethyl acetate and buthanol. In reducing power, different concentrations of samples were mixed with phosphate buffer, ferrocyanate, TCA and ferric chloride. Different concentrations of samples were mixed with DPPH and after 30 min the absorbances were measured. For determination of phenolic content, 500 µl of sample was mixed with Folin-Ciocalteu and sodium carbonate. For determination of flavonoids, 500 µl of sample was mixed with 2 ml of distilled water, NaNO2 and NaOH. In reducing power method, chloroform fraction showed the highest reducing capacity. In the DPPH radical scavenging method, the highest antioxidant capacity was found in buthanol fraction (IC50=84.42±1.8 µg/ml). In FRAP method, the highest antioxidant capacity was found in crude extract (5.4±0.3 mg/ml) and buthanol fractions (5.51±0.4 mg/ml), respectively. The highest amount of phenolic compounds was detected in ethyl acetate fraction of Myrtus communis (17.5±0.001 µg/g). The highest amount of flavonoids was found in crude extract of Myrtus communis (171.9±7.3 µg/ml). Overall, we can suggest that the leaves of Myrtus communis can be used as antioxidant and as a food additives to avoid oxidative degradation of foods.